Análise da expressão das proteínas PP2 em plantas com Huanglongbing e customização de um vetor de clonagem para silenciamento do gene PP2B10, por meio da tecnologia de RNA de interferência - D’Alessandre, Nathália Da Roz (2021)
Huanglongbing (HLB) is one of the major phytosanitary problems in today's citrus culture. The commercial varieties of oranges, tangerines and tangelos are considered susceptible to HLB, while Poncirus trifoliata and some of its hybrids are considered tolerant. HLB is caused by the bacterium Candidatus Liberibacter asiaticus (CLas) and the symptoms have been related to callose deposition and the accumulation of phloem proteins (PP2) in the phloem-stained element tubes o of the infected plant, causing the obstruction of the tubes and inhibiting the transport of photoassimilated throughout the plant. In Arabidopsis thaliana, as PP2 are encoded by 30 genes, which are divided into two groups (AtPP2-A1 to AtPP2-A15 and AtPP2-B1 to AtPP2-B15). In this work, the first objective was to evaluate an expression of six genes that code phloem proteins (PP2) in Citrus sinensis (highly susceptible) and Poncirus trifoliata (tolerant), infected with CLas. For the RT-PCR experiments, ten plants of C. sinensis and P. trifoliata are inoculated with bubbles infected with CLas (HLB+) and five plants inoculated with healthy bubbles. A positive reduction in the genes obtained in HLB+ plants was observed in comparison with plants not inoculated for C. sinensis. For P. trifoliata, only the pp2B10, pp2B13 and pp2B15 genes were regulated positively. Positive expression of all genes obtained in C. sinensis was also observed when compared to P. trifoliata. Based on the results, the pp2B10 gene was selected to be used as a target for silencing by means of interference RNA (RNAi) technology. Thus, the second objective also exists in this work, which has been customized a cloning vector, using RNAi technology, for silencing the pp2B10 gene in sweet orange (C. sinensis). For this, fragments of the target gene were cloned in opposite escorts in the vector pHANNIBAL, and later, the hairpin construction under the control of the 35S promoter was subcloned into the vector pCAMBIA2301. The construction pCAMBIA2301 + hairpinpp2B10 is being used for genetic transformation of sweet orange to confirm the function of the gene and obtain plants tolerant to HLB.